Where is my hand in space? The internal model of gravity influences proprioception - Gallagher, Maria (Biol Lett, 2021)
Knowing where our limbs are in space is crucial for a successful interaction with the external world. Joint position sense (JPS) relies on both cues from muscle spindles and joint mechanoreceptors, as well as the effort required to move. However, JPS may also rely on the perceived external force on the limb, such as the gravitational field. It is well known that the internal model of gravity plays a large role in perception and behaviour. Thus, we have explored whether direct vestibular-gravitational cues could influence JPS. Participants passively estimated the position of their hand while they were upright and therefore aligned with terrestrial gravity, or pitch-tilted 45° backwards from gravity. Overall participants overestimated the position of their hand in both upright and tilted postures; however, the proprioceptive bias was significantly reduced when participants were tilted. Our findings therefore suggest that the internal model of gravity may influence and update JPS in order to allow the organism to interact with the environment.